Citrate stabilized Fe3O4/DMG modified carbon paste electrode for determination of octamethylcyclotetrasiloxane in blood plasma and urine samples of cement factory workers - Rashid Heidarimoghadam (BMC Chemistry, 2020)
Abstract In this paper, a novel mercury-free electrochemical probe was constructed for the trace determination of octamethylcyclotetrasiloxane (D4) in some biological fluids by adsorptive stripping voltammetry. The platform is based on the adsorptive accumulation of Ni(II) onto a carbon paste electrode modified with citrate stabilized Fe3O4 (Cit-Fe3O4) and dimethylglyoxime (DMG). It was shown that trace levels of D4 enhance the electrochemical adsorptive stripping signal of Ni(II) on the electrode platform. It was shown that electrochemical signals are proportional to concentrations of D4. The supporting electrolyte, pH and instrumental parameters associated with the electrode response, including scan rate, accumulation potential and deposition time were optimized. The electrode platform demonstrated well resolved, reproducible peaks, with relative standard deviation (RSD) of 3.8% and detection limit (3Sb/m) of 27.0 ng/mL. The sensor exhibited good D4 detection and quantification in human blood plasma and urine samples.